2002
DOI: 10.1192/bjp.181.43.s91
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of cognitive-behavioural therapy in early schizophrenia: Acute-phase outcomes

Abstract: BackgroundCognitive–behavioural therapy (CBT) improves persistent psychotic symptoms.AimsTo test the effectiveness of added CBT in accelerating remission from acute psychotic symptoms in early schizophrenia.MethodA 5-week CBT programme plus routine care was compared with supportive counselling plus routine care and routine care alone in a multi-centre trial randomising 315 people with DSM–IV schizophrenia and related disorders in their first (83%) or second acute admission. Outcome assessments were blinded.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
300
0
13

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 329 publications
(322 citation statements)
references
References 19 publications
6
300
0
13
Order By: Relevance
“…Psychosocial treatments in early psychosis have been extensively studied, and there are positive findings pointing to the value of cognitive therapies in accelerating and maximizing symptomatic and functional recovery (81,82). Increasingly there has been attention to the fact that medications, while assisting in symptomatic recovery, do not, by themselves, contribute to a return to functioning.…”
Section: Stage 2: Early Detection and Treatment Of First Episode Psycmentioning
confidence: 99%
“…Psychosocial treatments in early psychosis have been extensively studied, and there are positive findings pointing to the value of cognitive therapies in accelerating and maximizing symptomatic and functional recovery (81,82). Increasingly there has been attention to the fact that medications, while assisting in symptomatic recovery, do not, by themselves, contribute to a return to functioning.…”
Section: Stage 2: Early Detection and Treatment Of First Episode Psycmentioning
confidence: 99%
“…The majority of the studies also concentrate on outpatients with chronic disorders, with the most notable exception being Drury et al (1996), which looked at a population of in-patients with a relatively recent onset of the disorder. The current Socrates trial (Lewis et al 2002), which focuses on treatment of recent onset patients, may well provide further information on the value of CBT for such patients.…”
Section: Cognitive Behaviour Therapymentioning
confidence: 99%
“…For comparison, in the band 1 arm, 275 would be needed in each arm for 90% power. Estimating that there would be a 15% dropout rate at 12 months (based on the outcome of the SoCRATES trial 181 ), it was concluded that the band 1 arm would need to recruit 564 patients in total.…”
Section: Data Analysis Band 1 Power Calculationmentioning
confidence: 99%